ISLAM DAN SOSIAL KONTROL: MENELISIK PENERAPAN SYARIAT ISLAM DI ACEH - Yusmalinda Yusmalinda; Syawaluddin Ismail; Muhammad Rusdi bin Muhammadiah; Muhammad Firdaus; Muhazir Muhazir (Jurnal el-Qanuniy: Jurnal Ilmu-Ilmu Kesyariahan dan Pranata Sosial, 2023)
The Aceh government has put Sharia into effect after receiving permission from the Indonesian government to enact Islamic law. The Aceh government took advantage of this chance to formally incorporate Islamic law into the nation's legal framework. This essay examines the development of Sharia and how it is used today. In this research, additional information in the shape of electronic information, rules, and government websites directly linked to the topics covered in this paper were used as data sources to learn more about Sharia in Aceh. This study incorporates various empirical studies carried out by earlier scholars in the form of papers, books, and other significant material to enhance the data and analysis. The findings of this study revealed that for more than 20 years, the application of Sharia had created a culture that was submissive to Islamic law, with the Acehnese Muslim community increasingly receiving instruction to uphold Sharia through the use of terminology from the "porch of Mecca". Communities that are not Muslim also help Aceh establish Sharia law. In addition to being founded on personal knowledge, adherence to Sharia is also made stronger by the legal penalties imposed for transgressions in the areas of creed, attire, and religion.